A meta‐analytic review of experimental tests of the interrogation technique of Hanns Joachim Scharff. Issue 2 (17th December 2020) - Luke, Timothy J.
Summary: Hanns Scharff, an interrogator during the Second World War, was known for his remarkable effectiveness at collecting intelligence from prisoners of war using a friendly, conversational approach in which he led the prisoners to unknowingly reveal the information he wanted. In the last decade, psychologists have produced a body of experimental studies testing the effectiveness of Scharff's interrogation technique. Here, I provide a meta‐analytic review of that experimental research. The existing data supports the conclusions that the present conceptualization of Scharff's technique is effective at eliciting more new information, leading people to perceive the interviewer as more knowledgeable, and inducing people to underestimate how much information they have revealed. However, numerous unanswered questions and challenges for this program of research remain. For example, future research may benefit from examining unaddressed elements of the methods Scharff used in the field. Research would also benefit from the development of measures that more clearly correspond to practical outcomes.